Clinical Usefulness of Haptoglobin Levels to Evaluate Hemolysis in Recently Transfused Patients - Shilpi Gupta; Kathleen Ahern; Fadi Nakhl; Frank Forte (Advances in Hematology)
Introduction. Haptoglobin binds the globin portion of free hemoglobin. Serum haptoglobin measurement is used as a laboratory marker for the diagnosis of hemolytic anemia. Since stored blood contains free hemoglobin, transfusion may affect haptoglobin levels. Study Objectives. The aim of the study was to evaluate whether serum haptoglobin could be measured to assess hemolysis in recently transfused patients. Patients and Methods. Twenty-one patients, receiving more than one unit of packed red blood cells (PRBCs) for presumed nonhemolytic indications, were enrolled. Serum haptoglobin levels were recorded before, immediately after, and 24 and 48 hours after transfusion. Observations and Results. Analysis of variance with a repeated measures was used to examine the serum haptoglobin levels at different time periods and no significant difference was found (P=.28). Conclusion. The results suggest that serum haptoglobin can be used in the diagnosis of hemolysis in patients receiving multiple units of PRBC.